"Most of my students kept saying, 'I never met a gay person'": A queer English language teacher's agency for social justice. (December 2018) - Leal, Priscila; Crookes, Graham V.
Abstract: This article presents an interview-based case study of a language teacher agency from social justice, queer, and ecological perspectives. We use Pantić's (2015) model of teacher agency for social justice to investigate four aspects (i.e., "sense of purpose, " "competence, " "autonomy, " "reflexivity") of Jackson's agency, a queer language teacher. A central driving force of Jackson's agency was her identification of contradictions between her sense of purpose and the educational structure in which her work was located, and thus her sense of purpose changed based on her context—from tending to her students' pastoral needs and to educating students about homophobia and Queer culture. Favorable conditions at the institutional and classroom levels enabled Jackson to exercise agency. They were a supportive department, an institution located in a liberal region, a conducive curriculum, student-teacher rapport, and timing of an instructional module (on LGBTQIA Rights). Jackson exercised agency particularly through the means of identity as pedagogy and also by changing the program's materials, by decentering herself as the sole holder of knowledge, and by coming out in the classroom.